Let’s Open the Media’s Black Box: The Media As a Set of Heterogeneous Actors and Not Only As a Homogenous Ensemble - Roulet, Thomas J.; Clemente, Marco (Academy of Management Review, 2018)
This commentary aims to complement and enrich Zavyalova and her colleaguesâ model by offering to consider the media as a set of heterogeneous actors, with their own motives and strategic decisions. The following development will make three key points: (i) Media reporting can be heterogeneous, often due to partisanship: A variance exists in eventsâ attention and presentation across media outlets. This variance is often not randomly distributed; different media outlets choose the cues that matter to them, and report them in a way that aligns with their motives and strategic goals. This is of crucial importance because: (ii) Different media outlets have different reaches: Media outlets reach broader or smaller audiences depending on whether these audiences have self-selected to follow these outlets. Thus, variances in perceptions among audiences can be due to the specific narrative an audience is exposed to. The previous two points are currently augmented by the recent surge of online and social media, which leads to: (iii) The media field has become more fragmented: Anyone can use social media and online platformsâsuch as Facebook or Twitterâto act as media themselves. This makes capturing media discourse more challenging.